Effect of Super-optimal Dose of NPK Fertilizers on Nutrient Harvest Index, Uptake and Soil Fertility Levels in Wheat Crop under a Maize (Zea mays L.)-Wheat (Triticum aestivum L. Cropping System) - Rakshit, Rajiv; Patra, A. K.; Purakayastha, T. J.; Singh, R. D.; Pathak, H.; Dhar, Shiva (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted in an Inceptisol (IARI, New Delhi, India) during 2010-2011 and 2011-2012 to investigate the effect of optimal (100% NPK) to super-optimal doses (200% NPK) of mineral fertilizer on yield attributes, nutrient harvest index and their uptake pattern in wheat (Triticum aestivum) crop under a maize-wheat cropping systems. Ten levels of fertilizer N, P and K along with 3% foliar spray of iron were laid out in a randomized manner in three replications. Proportionate increase in fertilizer doses of NPK increases the wheat grain (+5.4-5.6%) and straw yield (+5.1- 6.1%), but the rate of increase in yield declines as we move from lower to higher doses. The change or increased yield under treatments representing higher doses of NPK is attributed to the increase number of spikes (+4.7-56%) and the weight of grains in each spike (+5-6%). Super-optimal dose of mineral fertilizers (200% NPK) application increased the nutrient contents and uptake of nutrients in grain and straw of wheat. Fertility status of soil after the harvest of two cycles of maize-wheat crop increased with increased application of N, P and K. Nutrient harvest indices for various nutrients showed the effectiveness of mineral fertilizers and foliar iron application increased iron harvest index+9-20%.